2020
DOI: 10.1159/000506905
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Parasellar Lesions

Abstract: The parasellar region, located around the sella turcica, is an anatomically complex area representing a crossroads for important adjacent structures. Several lesions, including tumoral, inflammatory vascular, and infectious diseases may affect this area. Although invasive pituitary tumors are the most common neoplasms encountered within the parasellar region, other tumoral (and cystic) lesions can also be detected. Craniopharyngiomas, meningiomas, as well as Rathke's cleft cysts, chordomas, and ectopic pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 75 publications
0
20
0
2
Order By: Relevance
“…The parasellar region is an anatomically complex area that represents a crucial crossroads for important adjacent structures. 1 However, although the sellar region has specific anatomical landmarks, the parasellar region is not clearly delineated. 2 Most studies describe this area as being surrounded laterally by the dural walls of the cavernous sinus, containing the intra-cavernous portion of the internal carotid artery, cranial nerves III, IV and VI, and the V1 and V2 branches of the trigeminal nerve, inferiorly by the basisphenoid and sphenoid sinus, and superiorly by the suprasellar subarachnoid spaces containing the optic nerves and chiasm, hypothalamus, tuber cinereum and anterior third ventricle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parasellar region is an anatomically complex area that represents a crucial crossroads for important adjacent structures. 1 However, although the sellar region has specific anatomical landmarks, the parasellar region is not clearly delineated. 2 Most studies describe this area as being surrounded laterally by the dural walls of the cavernous sinus, containing the intra-cavernous portion of the internal carotid artery, cranial nerves III, IV and VI, and the V1 and V2 branches of the trigeminal nerve, inferiorly by the basisphenoid and sphenoid sinus, and superiorly by the suprasellar subarachnoid spaces containing the optic nerves and chiasm, hypothalamus, tuber cinereum and anterior third ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, other nontumourous lesions involving the parasellar region include inflammatory, granulomatous, infectious and vascular pathologies. 1,4,7 In Non-adenomatous sellar/parasellar lesions do not present with hypersecretory syndromes but rather with symptoms of mass effects as a result of compression of surroundings structures and/or hypopituitarism. 8 Visual loss is a common presenting complaint as a result of the proximity of these tumours to the optic nerves, chiasm and optic tracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright © 2019 the authors sometimes may not lead to a confirmed etiological diagnosis because of the uncertainty of the origin of a lesion (13). Diffusion weighted imaging (DWI) can non-invasively provide information concerning high signal-intensity regions as areas of increased cellularity and tissue microstructures by measuring water diffusion within a tissue (14)(15)(16), which is closely associated with membrane integrity and cell density (15,17).…”
Section: Page 4 Of 27mentioning
confidence: 99%
“…Wu et al (12) reported that quantitative dual-energy CT imaging, iodine content, slope of HU curve, and mean CT value may be valuable parameters for diagnostic differentiation between sellar meningiomas and pituitary adenomas. MRI was mainly performed as the examination of choice for the diagnosis of sellar lesions (13). Some MRI characteristics, such as visibility of the pituitary gland, contrast enhancement, and sellar enlargement can help differentiate pituitary macroadenomas from sellar meningiomas (8).…”
Section: Introductionmentioning
confidence: 99%